An Efficient, “Burn in” Free Organic Solar Cell Employing a Nonfullerene Electron Acceptor - Zhe Li (Advanced Materials, 2017)
A comparison of the efficiency, stability, and photophysics of organic solar cells employing poly[(5,6-difluoro-2,1,3-benzothiadiazol-4,7-diyl)-alt-(3,3′″-di(2-octyldodecyl)-2,2′;5′,2″;5″,2′″-quaterthiophen-5,5′″-diyl)] (PffBT4T-2OD) as a donor polymer blended with either the nonfullerene acceptor EH-IDTBR or the fullerene derivative, [6,6]-phenyl C71 butyric acid methyl ester (PC71BM) as electron acceptors is reported. Inverted PffBT4T-2OD:EH-IDTBR blend solar cell fabricated without any processing additive achieves power conversion efficiencies (PCEs) of 9.5 ± 0.2%. The devices exhibit a high open circuit voltage of 1.08 ± 0.01 V, attributed to the high lowest unoccupied molecular orbital (LUMO) level of EH-IDTBR. Photoluminescence quenching and transient absorption data are employed to elucidate the ultrafast kinetics and efficiencies of charge separation in both blends, with PffBT4T-2OD exciton diffusion kinetics within polymer domains, and geminate recombination losses following exciton separation being identified as key factors determining the efficiency of photocurrent generation. Remarkably, while encapsulated PffBT4T-2OD:PC71BM solar cells show significant efficiency loss under simulated solar irradiation (“burn in” degradation) due to the trap-assisted recombination through increased photoinduced trap states, PffBT4T-2OD:EH-IDTBR solar cell shows negligible burn in efficiency loss. Furthermore, PffBT4T-2OD:EH-IDTBR solar cells are found to be substantially more stable under 85 °C thermal stress than PffBT4T-2OD:PC71BM devices.